The Effect of Commitment and Compensation on Air Traffic Controller (ATC) Performance with Job Satisfaction as an Intervening Variable at the Air Nav Indonesia Palembang Branch - Sadewa, Gilang; Christian , Ferdinandus; Astini, Rina (East Asian Journal of Multidisciplinary Research, 2024)
This study focuses on discussing the effect of work commitment, work compenstation on the performance of air traffic controller with job satisfaction as an intervening variable at the AirNav Indonesia, Palembang. The type of research used is quantitative with a causal study design. Data collection through questionnaires and analyzed using multivariate-Structural Equation Model analysis. The researcher employed job satisfaction as an intermediary variable to investigate the impact of commitment and compensation on ATC performance in this study. The data analysis revealed that ATC performance is positively and significantly influenced by job satisfaction and commitment, while compensation does not have a significant direct impact on ATC performance. Additionally, the data analysis results demonstrated that compensation has a substantial and beneficial effect on job satisfaction, which in turn indirectly influences ATC performance. As a result, it is feasible to conclude that compensation and commitment are indispensable variables that significantly impact ATC performance, both directly and indirectly, via employment satisfaction.